STUDI PEMBUATAN YOGHURT SARI BIJI NANGKA (Artocarpus heterophyllus) DENGAN PENAMBAHAN KACANG MERAH (Phaseolus vulgaris L.) - Aceng Sehat; Usman Pato; Netti Herawati (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
Jackfruit and red beans are frequently found and cultivated in the tropical area, like Indonesia. The research was conduted from Mei to August 2014 in the Laboratory of Analytical of Agricultural Productsand Laboratory of Processing of Agricultural Products, Faculty of Agriculture, University of Riau, Pekanbaru. The study was conducted using Completely Randomised Design (CRD) with 4 treatments and 4 replications. The treatment were ratio of jackfruit seed and red beans namely 100 g : 0 g, 90 g : 10 g, 80 g : 20 g and 70 g : 30 g.Parameters analyzed were protein, fat and ash contents, total lacticacid, pH, total lactic acid bacteri, hedonic and descriptive organoleptic test of flavour, taste and texture. The results indicate that the ratio of jackfruit seed and red beans had highly significant effect on protein, fat and ash contents, total lactic acid, pH, total lactic acid bacteria and hedonicorganoleptic value of flavor. The ratio of jackfruit and red bean extracts did not have significant effect on hedonic organoleptic value of taste and texture, descriptive organoleptic value of flavour, taste, and texture. The best treatment was P2 with ratio 90 g of jacfruit and 10 g of red bean. Keywords : Yoghurt,Jackfruit seed, red bean, quality.